The State of Teaching Geography in Ukraine Since the Change of Political Regime - Fodor Gyula; Фодор Дюло (Taylor & Francis, 2003)
Abstract. The demise of the USSR and the birth of Ukraine as an independent nation have brought about significant changes in the education aims and curricula of geog- raphy. The monopolistic ideology of state socialism has disappeared. There are, however, still serious constraints on the freedom of teaching due to the poor economic situation of the country and the shortage of up-to-date textbooks for ethnic minorities.
Стан навчання географії в Україні після зміни політичної системи
Keywords: Soviet Union; Ukraine; school education; teaching Geography